2013
DOI: 10.1155/2013/950273
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of Apoptotic Cells by Macrophages Induces Regulatory Phenotype and Involves Stimulation of CD36 and Platelet-Activating Factor Receptor

Abstract: Phagocytosis of apoptotic cells (efferocytosis) induces macrophage differentiation towards a regulatory phenotype (IL-10high/IL-12p40low). CD36 is involved in the recognition of apoptotic cells (AC), and we have shown that the platelet-activating factor receptor (PAFR) is also involved. Here, we investigated the contribution of PAFR and CD36 to efferocytosis and to the establishment of a regulatory macrophage phenotype. Mice bone marrow-derived macrophages were cocultured with apoptotic thymocytes, and the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 31 publications
(45 reference statements)
2
45
1
4
Order By: Relevance
“…9 In addition, our results indicate unaltered TSP-1 expression in EDE conjunctiva with significantly reduced CD36 expression, in contrast to the increased CD36 expression in TSP-1-deficient conjunctiva. Several in vitro studies have reported expression of both proinflammatory 37,38 and antiinflammatory [39][40][41] cytokines in macrophages resulting from the ligation of CD36 by ligands, such as apoptotic cells, oxidized low-density lipoprotein, and TSP-1, but not on epithelial cells. However, in vivo studies appear to predominantly support the anti-inflammatory role of CD36.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, our results indicate unaltered TSP-1 expression in EDE conjunctiva with significantly reduced CD36 expression, in contrast to the increased CD36 expression in TSP-1-deficient conjunctiva. Several in vitro studies have reported expression of both proinflammatory 37,38 and antiinflammatory [39][40][41] cytokines in macrophages resulting from the ligation of CD36 by ligands, such as apoptotic cells, oxidized low-density lipoprotein, and TSP-1, but not on epithelial cells. However, in vivo studies appear to predominantly support the anti-inflammatory role of CD36.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, it was shown that clearance of dying cells by tumour macrophages shifts them towards the pro tumorigenic M2 phenotype by mechanisms involving the receptor for the lipid mediator plateletactivating factor (PAF), a member of the 1alkyl,2acylglycerophosphocholine subclass of lipids 4 . Lipid mediators are generated in the tumour microenvironment and can modu late tumour growth.…”
mentioning
confidence: 99%
“…Our previous studies pointed to a central role for PAFR in this process. We found that CD36 co-localizes with PAFR in macrophage plasma membrane lipid rafts for optimal oxLDL uptake and apoptotic cells phagocytosis (14,15). The association of these receptors shifted macrophages towards the anti-inflammatory phenotype.…”
Section: Discussionmentioning
confidence: 87%
“…The adipose tissue presented higher mRNA levels of some M1 markers, increased IL-12 and reduced IL-10 levels. The balance of IL-12 and IL-10 had been previously employed to establish the macrophages phenotype: the classically activated or M1 macrophages and the alternatively activated or M2 (14,16,30). The deficiency of PAFR also resulted in weight gain, reduced glucose tolerance, increased expression of Ldlr in the liver and hepatocyte disarrangement, hepatic insulin resistance, and increased glucose levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation